Phenolic Profile, Nutritional Composition, Functional Properties, and Antioxidant Activity of Newly Grown Parthenocarpic and Normal Seeded Tomato - Sajid Dominic; Abdullah Ijaz Hussain; Shahzad Ali Shahid Chatha; Qasim Ali; Nosheen Aslam; Satyajit Dey Sarker; Saeed Ahmad Shah Chishti; Shafaqat Ali; Saliha Maqbool; Mohamed A. El-Sheikh; Mohammed Nasser Alyemeni (Journal of Chemistry)
The aim of the study was to compare the physicochemical parameters, sugar, vitamin C, and phenolic profiles in five genotypes of local indeterminate tunnel tomato hybrid (LITTH) (LITTH-778, LITTH-784, LITTH-786, LITTH-788, and LITTH-790) of natural parthenocarpic tomato (NPT) and normal seeded tomato (NST). Samples were collected from the experimental fields of Ayub Agricultural Research Institute, Faisalabad, Pakistan. Physical parameters (fruit shape, fruit weight, fruit length, fruit width, number of seeds per fruit, and shelf-life) and chemical composition (moisture, ash, crude fat, crude fiber, total carbohydrate, crude protein, and vitamin C) of NPT and NST were analyzed by reported methods. The methanolic extracts of tomato pulp were prepared by shaking and extracts were assayed for antioxidant activity. Sugar contents and phenolic profile of NPT and NST were estimated using HPLC method. Weight and size of NPT were less and smaller than the NST. Moreover, NPT were seedless with longer shelf-life and had more phenolic and flavonoid contents than the NST. HPLC analysis revealed that chlorogenic acid, gallic acid, and p-coumaric acid were major phenolics in methanol (polar solvent) extracts of NST, and caffeic acid, gallic acid, and p-coumaric acid in NPT extract. NPT contained higher concentration of sugar contents, but lower concentration of vitamin C than NST. In 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay, NPT fruit extracts showed high scavenging activity with the 50% inhibitory concentration (IC50) value of 22.56 μg/mL compared to NST fruit extracts having IC50 29.49 μg/mL. This study provided useful information for farmers and nutritionists.